Heat Transfer Analysis in Heat Exchanger with Various Shifting Media - Endri Rizki Anugrah; Remon Lapisa; Arwizet K; Ambiyar Ambiyar (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
Solar panels (photovoltaics) function to absorb sunlight exposure to be converted into electrical energy. But if the heat received over the sun, it will reduce the electrical power of the solar panels. Therefore, a heat transfer device is required to maintain the temperature of the solar panels always in the optimal condition to work. The measurement results show that the average temperature out of the panel (T1) is greater than in the panel (T2), the upper temperature of the tank (T5) is greater than the bottom temperature of the tank (T6), and the average temperature value in the tank (T4) is between the upper temperature of the tank (T5) and the bottom temperature of the tank (T6) of any variation of the sender's media. Meanwhile, the difference between the entry temperature (T2) and the exit temperature (T1) in the study indicates how well the medium of the conducter absorbs excessive heat. Then it can be concluded that the medium of coolant is the best conducter media to absorb and conduct heat because it has a difference out panel (T1) and in panel (T2 amounted to 6.522 °c from Air Aki soft-0.0375 ° C, and water ordinary 1.069 °c. Panel surya (Photovoltaic) berfungsi menyerap paparan cahaya matahari untuk diubah menjadi energi listrik. Namun jika panas matahari yang diterima berlebih, akan mengurangi daya listrik hasil panel surya tersebut. Maka dari itu diperlukan sebuah alat pemindah panas yang mampu menjaga suhu panel surya selalu didalam keadaan optimal untuk bekerja. Hasil pengukuran menunjukkan bahwa rata-rata suhu out panel (T1) lebih besar daripada in panel (T2), suhu atas tangki (T5) lebih besar daripada suhu bawah tangki (T6), dan nilai rata-rata suhu in tangki (T4) berada diantara suhu atas tangki (T5) dan suhu bawah tangki (T6) dari setiap variasi media penghantar. Sementara selisih dari suhu masuk (T2) dan suhu keluar (T1) pada penelitian mengindikasikan seberapa bagus media penghantar dalam menyerap panas yang berlebih. Maka dapat disimpulkan media penghantar coolant adalah media penghantar yang paling baik dalam menyerap dan menghantarkan panas karna memiliki selisih out panel (T1) dan in panel (T2 sebesar 6,522 °C daripada Air Aki Lunak sebesar –0,0375 °C, dan Air biasa 1,069 °C.